Peningkatan Pengetahuan Dan Keterampilan Melakukan Aktivitas Fisik Untuk Menurunkan Gangguan Fisik Pada Masa Premenopause - Cahyani Ari Lestari, Nur; Zulhijriani, Zulhijriani (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Premenopause is a transitional period characterized by various physical disorders such as hot flashes, sleep disorders, and joint pain. Research in Tondomulyo Village showed 67.3% of women have low levels of physical activity with an average duration of only 86.4 minutes per week, far below WHO recommendations. The purpose of this community service is to increase knowledge and skills in performing physical activities to reduce physical disorders during premenopause. The service method used a participatory approach with brainstorming, lectures, question and answer sessions, and demonstrations conducted in 4 meetings over 1 week targeting 30 premenopausal women aged 40-55 years and 12 health cadres. The program included education about premenopause, demonstration of physical activities including aerobic exercises, strength training, yoga, and empowerment of health cadres. Results showed a very significant increase in knowledge from an average pretest score of 45.33 to posttest 79.67 with a 75.8% increase. Statistical tests showed significance value p=0.000 (p<0.001). Skills evaluation showed 93.3% of participants were able to perform aerobic exercises, 100% were able to do simple strength training, 86.7% were able to perform basic yoga movements, and 83.3% were able to combine all three. The program successfully formed 3 physical activity groups based on areas. Conclusion the physical activity education program proved to be very effective in increasing the knowledge and skills of premenopausal women with a 100% success rate and very high statistical significance.